2005
DOI: 10.1002/jmv.20313
|View full text |Cite
|
Sign up to set email alerts
|

The importance of HCV on the burden of chronic liver disease in Italy: A multicenter prevalence study of 9,997 cases

Abstract: Knowledge of the current epidemiology of chronic liver disease in Italy is mostly obsolete and fragmentary for the lack of up-to-date consistent data. In 2001, a 6-month prevalence study was undertaken in 79 hospitals to assess the characteristics of chronic liver disease in Italy. Both prevalent and incident cases were enrolled. A total of 9,997 patients were recruited, of whom 939 (9.4%) had normal liver biochemistry, 6,210 (62.1%) had chronic hepatitis, 1,940 (19.4%) had liver cirrhosis, and 341 (3.4%) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 19 publications
4
64
0
3
Order By: Relevance
“…A multicentre case-control study on the aetiology of symptomatic cirrhosis showed that alcohol intake was responsible for the highest proportion of cases, followed by HCV and HBV infection, and the three risk factors together accounted for 85.5% of the total cases (Corrao et al, 1998c). In agreement with these results, the population-based Dionysos study showed that the same factors were responsible for 92.4% of all the cases of cirrhosis and HCC in the area, considering >30 g/day of ethanol as a risk factor for liver diseases (Bellentani and Tiribelli, 2001), and a recent multicentre Italian study found that only 6.4% of 341 HCC cases had neither HBV or HCV infection nor alcoholic liver disease (Sagnelli et al, 2005).…”
Section: Diabetes and Hepatocellular Carcinomasupporting
confidence: 60%
See 1 more Smart Citation
“…A multicentre case-control study on the aetiology of symptomatic cirrhosis showed that alcohol intake was responsible for the highest proportion of cases, followed by HCV and HBV infection, and the three risk factors together accounted for 85.5% of the total cases (Corrao et al, 1998c). In agreement with these results, the population-based Dionysos study showed that the same factors were responsible for 92.4% of all the cases of cirrhosis and HCC in the area, considering >30 g/day of ethanol as a risk factor for liver diseases (Bellentani and Tiribelli, 2001), and a recent multicentre Italian study found that only 6.4% of 341 HCC cases had neither HBV or HCV infection nor alcoholic liver disease (Sagnelli et al, 2005).…”
Section: Diabetes and Hepatocellular Carcinomasupporting
confidence: 60%
“…The role of alcohol intake may be lower in other Mediterranean areas, however, as shown by the different proportions of HCC cases with alcoholic liver disease in various parts of Italy in the mentioned multicentre Italian study (Sagnelli et al, 2005), and by the lower proportion of HCC cases with alcohol intake >60 g/day in the Greek study (Kuper et al, 2000b) compared to the Brescia HCC study.…”
Section: Diabetes and Hepatocellular Carcinomamentioning
confidence: 94%
“…HCV is the most important cause of chronic liver disease in Italy and is found in nearly 70% of cases [Sagnelli et al, 2005]. Infection with HCV persists in about 75% of cases and causes various degrees of liver inflammation and fibrosis; in time it may lead to cirrhosis and hepatocellular carcinoma [Poynard et al, 2003;Kumada et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of the seropositive cases is 44.9 years also indicating active part of life and like HBV it is also true that this positivity will create reduction in activity, induce economic and social burden for the patient and his family. This seropositivity for HCV is less than that of Pakistan 9 , Kenya 13 , Thialnd 15 and same in Italy 14 where the prevalence of HCV is 6%, 7.1%, 7.8% and 5.7% respectively. This difference may be due to small sample number, not done in general population.…”
Section: Resultsmentioning
confidence: 68%
“…Our seropositivity is less than that of Pakistan 9 and Kenya 13 where the seropositivity found is 10% and 26.2% respectively. The prevalence is also higher in Italy where the prevalence of HBsAg is 13.4% 14 .…”
Section: Resultsmentioning
confidence: 94%